Exploring musculoskeletal disorders and ergonomic challenges among software professionals: A cross sectional study - Ruchi Chaturvedi; Sumaiya Ahmad; Shweta Rajpal; Avi Singh; Jamal Masood (Journal of Family Medicine and Primary Care)
Background: Musculoskeletal disorders (MSDs) significantly affect global health, with a high prevalence among software professionals due to prolonged sedentary behaviour and suboptimal ergonomic practices. In India, limited research exists on the burden and ergonomic challenges of MSDs in the IT sector, necessitating this study. Materials and Methods: An analytical cross-sectional study was conducted among 200 software professionals employed in multinational companies in India. Data were collected over 6 months using an online self-administered questionnaire comprising sociodemographic details, ergonomic practices and the Nordic Musculoskeletal Questionnaire (NMQ). Purposive sampling and snowball techniques ensured participant diversity. Descriptive statistics summarized data, while logistic regression identified significant predictors of MSDs. Results: The prevalence of MSDs was 72% during last 12 months with the lower back (66.7%) and neck (56.9%) being the most affected regions. Women were at a significantly lower risk (OR = 0.403, P = 0.049), while overweight individuals faced higher risks (OR = 2.84, P = 0.011). Prolonged work hours (≥8 hours/day) were a significant predictor (OR = 3.175, P = 0.004). Ergonomic challenges included inadequate workstation setups, with only 65% having a dedicated workspace and 45% receiving ergonomic training. Coping strategies included stretching exercises (61%) and over-the-counter medications (49.3%). Conclusion: The study highlights a significant burden of MSDs among Indian software professionals, emphasizing the need for workplace interventions focusing on ergonomic training, improved workstation design, and awareness about early medical consultation. Future research should assess the efficacy of these strategies to mitigate MSD risks and enhance occupational health outcomes.